2018
DOI: 10.1177/0963689718766324
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Human Placenta-Derived Neural Cells on Neuroprotection and the Inhibition of Neuroinflammation in a Rodent Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common age-related neurodegenerative disease in the elderly and the patients suffer from uncontrolled movement disorders due to loss of dopaminergic (DA) neurons on substantia nigra pars compacta (SNpc). We previously reported that transplantation of human fetal midbrain-derived neural precursor cells restored the functional deficits of a 6-hydroxy dopamine (6-OHDA)-treated rodent model of PD but its low viability and ethical issues still remain to be solved. Albeit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 66 publications
0
35
0
1
Order By: Relevance
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, 2017;Han et al, 2018;X. Wang, Ma, et al, 2018), DDD (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018), MS (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018), PD (Jamali et al, 2018;H. Kim, Lee, et al, 2018), and RDD (Mead, Amaral, & Tomarev, 2018), as summarized in Table 2.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, transplanted neural progenitor cells (NPCs) can play a bystander effect of neural protection and immune regulation in addition to the role of cell replacement, thus promoting tissue repair by prevention of tissue damage, interfering with pathogenic processes, or saving endogenous nerve cells (De Feo et al, 2012). Additionally, different studies have confirmed other bystander effects induced by NSCs, such as ameliorating damage to neurophysical structures, immunoregulation (Kim et al, 2018) , neuroprotection (Cui et al, 2015;Pang et al, 2017), neurotrophication (Bernstock et al, 2017;Marsh and Blurton-Jones, 2017) and angiogenesis (Boese et al, 2018), as well as by having an endogenous impact in disease models (Jablonska et al, 2016) .…”
Section: The Therapeutic Mechanism Of Neural Stem Cell Transplantationmentioning
confidence: 99%